THE IMPACT OF DIGITAL TRANSFORMATION ON THE INVESTMENT CLIMATE AND ASSESSMENT OF PREFERENCE AND RISK FACTORS (DESCRIPTIVE ANALYTICAL STUDY) BY APPLYING TO EGYPT AS A MODEL (World Bulletin of Social Sciences, 2021)
During the past decades, there have been tremendous technological developments in all human fields, financial institutions and banks have developed fundamentally, as technological devices and communications devices have been introduced, and the volume of data and information has been expanded, which has increased the complexity of its management, digital transformation has become one of the pillars of investment in financial institutions due to the provided data that helps and benefits the investors and facilitates the geographical expansion of the institution's activity as a result of the development of financial applications and depending on targeted advertising for new segments of consumers. In this research, we wanted to present the impact of digital transformation on the investment climate, with an assessment of preference factors, by applying to Egypt, in topic one of the research, we dealt with the theoretical framework of digital transformation, its nature and role in financial institutions and banks, its various techniques, risks, and precautionary methods used to avoid the occurrence of various risks, while presenting the steps of successful digital transformation. in organizations and the definition of modern digital management of financial institutions and the role of digital transformation in investing in banking institutions. In topic two, we applied the study to Egyptian banks using a questionnaire form that was distributed to 140 employees and managers in Egyptian banks, the questionnaire was distributed to the sample members and 132 questionnaires were retrieved from them and then We analyzed the results and the descriptive analytical method was followed during the study.
Keywords: Digital transformation; Investment climate; Competitiveness; Banks